The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.5489/cuaj.5348
|View full text |Cite
|
Sign up to set email alerts
|

Use of Robotic Anastomosis Competency Evaluation (RACE) tool for assessment of surgical competency during urethrovesical anastomosis

Abstract: Trainee RACE scores improved and proportion of UVA performed by trainees increased over time. RACE can be used as an objective measure of surgical performance during training. Strict mentor supervision allowed safe training without compromising patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Two blinded surgeons assessed the anonymised video recordings of the task, using the GEARS and Robotic Anastomosis Competency Evaluation (RACE) [ 29 ] scores. The 14 participants were stratified, this time into two groups by caseload, into expert and novice groups.…”
Section: Discussionmentioning
confidence: 99%
“…Two blinded surgeons assessed the anonymised video recordings of the task, using the GEARS and Robotic Anastomosis Competency Evaluation (RACE) [ 29 ] scores. The 14 participants were stratified, this time into two groups by caseload, into expert and novice groups.…”
Section: Discussionmentioning
confidence: 99%
“…RACE is a RARP‐specific tool that has been used to evaluate UVA in both simulation and live surgery . Khan et al demonstrated improved RACE scores for those with greater clinical experience during their training on live patients. While RACE scores identify task‐specific assessment of the UVA, there remains a subjective component for standardized assessment, such as dexterity or needle positioning during anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…It also remains reliant on assessor subjectivity and human rating which introduces the risk of bias [ 4 ]. Another tool, the Robotic Anastomosis Competency Evaluation (RACE), is a validated, objective scoring system to assess surgical performance during ureterovesical anastomosis (UVA) and provide structured feedback [ 9 ]. Whilst UVA is a critical step in surgical procedures, such as robot-assisted radical prostatectomy (RARP), it represents one task and not an entire procedure [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another tool, the Robotic Anastomosis Competency Evaluation (RACE), is a validated, objective scoring system to assess surgical performance during ureterovesical anastomosis (UVA) and provide structured feedback [ 9 ]. Whilst UVA is a critical step in surgical procedures, such as robot-assisted radical prostatectomy (RARP), it represents one task and not an entire procedure [ 9 , 10 ]. Collectively, there is a need for clinically relevant objective metrics which can quantify a surgeon’s performance, provide feedback and ultimately improve both surgical and patient outcomes.…”
Section: Introductionmentioning
confidence: 99%